2023
DOI: 10.3389/fendo.2023.1167317
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum water-soluble vitamin exposures with the risk of metabolic syndrome: results from NHANES 2003-2006

Abstract: IntroductionExisting evidence suggests an association between certain vitamins and metabolic syndrome (MetS), but few epidemiological studies have focused on the effects of multivitamin co-exposure on MetS. This study aims to investigate the associations of the individual or multiple water-soluble vitamins (i.e., vitamin C (VC), vitamin B9 (VB9), and vitamin B12 (VB12)) with co-exposure to MetS, as well as the dose-response relationships among them.MethodsA cross-sectional study was conducted by employing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous studies have illustrated that co-exposure to a mixture of nutrients, including β-carotene, vitamin A, vitamin D, vitamin C, α-tocopherol, folate, vitamin B6, and vitamin B12, could diminish the risk of all-cause mortality in diabetic patients ( 27 ). Furthermore, the combined effects of vitamin C, vitamin B9, and vitamin B12 could limit the risk of metabolic disorders ( 28 ). Researchers demonstrated that adherence to a mineral-based nutrient pattern, which refers to the inclusion of multiple vitamins and minerals in an individual’s daily diet, was associated with healthier metabolic factors ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have illustrated that co-exposure to a mixture of nutrients, including β-carotene, vitamin A, vitamin D, vitamin C, α-tocopherol, folate, vitamin B6, and vitamin B12, could diminish the risk of all-cause mortality in diabetic patients ( 27 ). Furthermore, the combined effects of vitamin C, vitamin B9, and vitamin B12 could limit the risk of metabolic disorders ( 28 ). Researchers demonstrated that adherence to a mineral-based nutrient pattern, which refers to the inclusion of multiple vitamins and minerals in an individual’s daily diet, was associated with healthier metabolic factors ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ketema et al ( 28 ) adopted BKMR analysis to show that a mixture of phthalate metabolites was associated with eczema in 7-year-old children. A cross-sectional study found that co-exposure to water-soluble vitamins was associated with a lower risk of metabolic syndrome based on the qgcomp model and that vitamin C provided the greatest negative weight to the qgcomp index ( 29 ). In this study, we found a positive association between co-exposure to vitamins A, C, B 6 , B 12 , D, and E and eczema in children, with vitamin B 6 as the highest positive weighted vitamin.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of living standards, metabolic diseases have been rampant worldwide. These diseases are closely related to high-fat diets (HFD) and pose a serious public health problem, leading to increased incidence and severity of chronic diseases such as obesity, diabetes, dyslipidemia, non-alcoholic fatty liver disease (NAFLD), hypertension, and hyperuricemia, as well as premature death ( 1 , 2 ). By 2025, the global obesity rate is projected to reach around 20%, with severe obesity exceeding 6% ( 3 ).…”
Section: Introductionmentioning
confidence: 99%